Evaluation of Routine Health Examination for Screening Primary Open Angle Glaucoma in Eastern China: A Hospital-Based Cross-Sectional Study - Fang Y; Cheng J; Zhu L; Xiao M; Sun X (Dove Medical Press, 2020)
Yuan Fang,1,* Jingyi Cheng,1,* Li Zhu,1 Ming Xiao,2 Xinghuai Sun1,3– 5 1Department of Ophthalmology and Visual Science, Eye and ENT Hospital, Shanghai Medical College, Fudan University, Shanghai 200031, People’s Republic of China; 2Department of Ophthalmology, Shanghai Bei Zhan Hospital, Shanghai 200070, People’s Republic of China; 3Shanghai Key Laboratory of Visual Impairment and Restoration, Shanghai 200031, People’s Republic of China; 4NHC Key Laboratory of Myopia, Chinese Academy of Medical Sciences (Fudan University), Shanghai 200031, People’s Republic of China; 5State Key Laboratory of Medical Neurobiology, Institutes of Brain Science and Collaborative Innovation Center for Brain Science, Fudan University, Shanghai 200032, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinghuai SunDepartment of Ophthalmology and Visual Science, Eye and ENT Hospital, Shanghai Medical College, Fudan University, Shanghai 200031, People’s Republic of ChinaTel +86 21 64377134Email xhsun@shmu.edu.cnPurpose: To evaluate the effect of routine health examination (RHE) for screening primary open angle glaucoma (POAG) in Eastern China.Materials and Methods: We enrolled patients with newly diagnosed and untreated POAG admitted to the Eye, Ear, Nose and Throat Hospital of Fudan University, Shanghai, China. Patients who were screened on RHE and then diagnosed with POAG were classified into the RHE group. The rest were classified as the non-RHE group. Demographic and ocular characteristics, 24-hour intraocular pressure (IOP), and glaucoma grade classified as the mild, moderate and severe groups according to glaucomatous optic neuropathy evaluated based on the enhanced Glaucoma Staging System were compared between the two groups.Results: In total, 172 patients with POAG (74 cases in the RHE group and 98 cases in the non-RHE group) were enrolled. The average age of patients in the RHE and non-RHE groups was 47.53 ± 1.48 years and 51.47 ± 1.46 years, respectively (P = 0.064), while the average mean deviation (MD) was 5.98 ± 0.66 dB and 9.79 ± 0.80 dB (P = 0.001), respectively. The frequency of mild, moderate and severe grade glaucoma in the RHE group was 47.3%, 36.5%, and 16.2%, respectively, while that in the non-RHE group was 27.6%, 31.6%, and 40.8%, respectively (P = 0.001). The presumed visual field MD progression rate for Chinese patients with untreated POAG was 0.97 dB/year. Additionally, the 24-hour IOP curve in the two groups was similar, with the exception of the IOP at 10:00 PM and 2:00 AM, which was higher in the RHE group than that in the non-RHE group.Conclusion: Our study showed RHE was an important and practical method to screen for POAG in Eastern China. RHE also assisted with an earlier diagnosis of POAG and may assist in preventing visual field loss.Keywords: primary open angle glaucoma, screening, routine health examination, visual field progression